COMPARATIVE ANALYSIS OF THE WEIGHT AND COSTS OF BUILDING A LIVING HOUSE USING CONVENTIONAL AND FERROCEMENT METHODS IN THE CITY OF PALANGKA RAYA - Rudi Waluyo; Nor Aidi Firdaus; Veronika Happy Puspasari (Universitas Udayana, 2024)
One of the latest engineering innovations, namely the ferrocement method for housing, supports the implementation of the Extreme Poverty Alleviation Program under the leadership of the President of the Republic of Indonesia. This is realized through Presidential Instruction Number 4 of 2022 which emphasizes the importance of the Ministry of Public Works and Public Housing in accelerating the eradication of extreme poverty. One step is to repair uninhabitable into habitable houses, utilizing ferrocement technology to meet structural resilience indicators in improving housing quality. This research aims to measure the weight of the house and analyze the difference cost of a livable house using the conventional method and the type 45 ferrocement method. The research was carried out from January to August 2023. The research location is in Palangka Raya City. The descriptive analysis will be used to determine the weight of the house and the planned budget for the cost of a habitable house using conventional and the ferrocement method. The results are that the weight of a type 45 habitable house using the conventional method is 87,220.56 kg and the weight of a type 45 habitable house using the ferrocement method is 82,306.52 kg. This shows a weight difference of 5,897.03 kg or 6 % and the cost of a type 45 habitable house using the conventional method is IDR. 322,696,812.10 and the cost of a habitable house type 45 using the ferrocement method is Rp. 272,539,766.29 shows a cost difference of Rp. 50,157,045.81 or amount 16 %.